Genesis and tectonic setting of the Late Devonian Tawuerbieke gold deposit in the Tulasu ore cluster, western Tianshan, Xinjiang, China. Issue 10 (27th July 2017) - Peng, Yi-Wei; Gu, Xue-Xiang; Lv, Peng-Rui; Zhang, Yong-Mei; Cheng, Wen-Bin; Wang, Xin-Li
ABSTRACT: The Tawuerbieke deposit is one of the important mining gold deposits in the Tulasu basin, which is known as an epithermal gold ore cluster in the Boluokenu Polymetallic Belt (BPB), western Tianshan, China. The orebodies of this deposit are hosted by late Palaeozoic volcanic rocks and granitic porphyries. LA-ICP-MS U–Pb dating on zircons from a hosting andesite gave a weighted average age of 367.1 ± 3.2 Ma. Geochemical characteristics of the Late Devonian volcanic rocks are similar to those of arc-type magma, which could be formed in a continental arc due to the North Tianshan oceanic plate southward subduction under the Yili-Central Tianshan plate. Diorite aplite dike crosscutting orebody has a late Carboniferous crystallization age (315.2 ± 3.5 Ma), constraining the mineralization age within the range of 367 ~ 315 Ma. Considering that all the other deposits with various types of mineralization in the BPB are products of the Late Devonian–early Carboniferous magmatism, we further suggest that the Tawuerbieke deposit formed during Late Devonian to early Carboniferous. Isotopic geochemistry data of S, Pb, C, and O suggest that the ore-forming materials were mainly derived from the host volcanic-subvolcanic rocks. The ore-hosting rock types, hydrothermal alteration, and ore mineral assemblage and textures of the Tawuerbieke distinctly differ from those of the low- and high-sulphidation epithermal Au deposits in the Tulasu basin, indicating that it could experience the telescoping/juxtaposing between porphyry- and epithermal-style mineralization. The epithermal- and porphyry-type Au mineralization in the Tawuerbieke deposit, together with the low- and high-sulphidation epithermal Au, porphyry Cu, and skarn-type Fe–Cu mineralization in the Tulasu basin, constitutes an epithermal–porphyry–skarn polymetallic mineralization system. The development of such mineralization system and magmatic-arc setting in the Tulasu basin suggests that porphyry-type Cu–Au mineralization should have a high potential at the deep sites of the Tawuerbieke district.